Edukasi Pentingnya Spiritual Care Anak di Era Digital di Kecamatan Laguboti Kabupaten Tapanuli Utara - Riris Johanna Siagian (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The role of parents in implementing spiritual care for children is becoming increasingly important amidst various social challenges, both internal and external. The implementation of Community Service (PkM) aims to determine the extent to which parents are aware of their duties and responsibilities regarding the spiritual care of children. This activity was carried out at the Hadassah Foundation, Laguboti District, North Tapanuli Regency, in collaboration with Lecturers and Students of the Master of Theology Study Program, HKBP Pematangsiantar Theological College. The methods used included spiritual care educational discussions with community leaders and supporting institutions and foundation administrators, as well as educational discussions with parents in Laguboti District. The results of the activity showed that spiritual guidance for children has not been optimally carried out by parents, due to the busyness of parents in working, the limited role of schools, and the minimal role of churches in providing spiritual guidance. Through this PkM activity, the team encouraged strengthening collaboration between parents and churches to pay more attention to children's spirituality on an ongoing basis. This activity is expected to become a model of integrated community-based spiritual guidance.